THE ROLE OF KARAWITAN EXTRACURRICULAR IN CULTIVATING THE CHARACTER OF LOVE FOR CULTURE AMONG ELEMENTARY SCHOOL STUDENTS - Sulistyawati, Anita; Putro, Ahmad Agung Yuwono (Ridwan Institute, 2024)
Karawitan extracurricular activities can be a means for character education. The purpose of this study is to examine the implementation of character education through extracurricular karawitan activities in elementary schools. This study uses a descriptive qualitative approach that aims to identify how the character of love for culture and cooperation are formed through the involvement of students in extracurricular activity. Data sources are obtained through direct observation, unstructured interviews, and the collection of documents related to school profiles, karawatan activities at SD Negeri Sendangharjo. The results show that the application of cultural love character values has a significant positive impact on children's social relationships and behavior at school, as well as strengthening the relationship between students, parents, and schools. The character of cooperation formed through karavatan in elementary school provides an important meaning in shaping the personality of Pancasila and plays a role in preserving and disseminating local culture. The application of the principles of cooperation and mutual cooperation is beneficial for strengthening social relations at school and developing students' social and cultural skills and involving parents in supporting children in art activities.